Global economy picking up - Ferdinand Fichtner; Guido Baldi; Christian Dreger; Hella Engerer; Stefan Gebauer; Michael Hachula; Malte Rieth (DIW Economic Bulletin, 2016)
The world economy is gaining momentum after sluggish growth in the first half 2016 - which was primarily due to a weak expansion in the emerging markets - gave way to a slight acceleration. This trend is likely to continue, and will increasingly benefit the developed economies as well. The brightening labor market situation in advanced countries is leading to a higher level of consumer demand, which will remain a primary growth driver. As a result of the improved sales opportunities, the currently weak corporate investment activity should pick up again. The growth of global economic output is expected to amount to 3.3 percent this year, and is expected to be slightly higher in the coming two years. This development will be supported by fiscal policy, while monetary policy is likely to become more contractionary globally in the course of further U. S. interest rate hikes. There remain significant risks, however - especially in Europe, where political uncertainty is high due to the Brexit decision and the upcoming elections in key EU member states, among other factors.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook